Pityriasis Rosea and Immunosuppressive Drugs [Letter] - Drago F; Fidanzi C; Ciccarese G (Dove Medical Press, 2024)
Francesco Drago,1 Cristian Fidanzi,2,3 Giulia Ciccarese4 1Dermatology Clinic, Casa di Cura Villa Montallegro, Genoa, Italy; 2Unit of Dermatology, Department of Medical and Oncological Area, University of Pisa, Pisa, Italy; 3Unit of Dermatology, Carrara Hospital, Carrara, Italy; 4Unit of Dermatology, Department of Medical and Surgical Sciences, University of Foggia, Foggia, ItalyCorrespondence: Giulia Ciccarese, Department of Medical and Surgical Sciences, University of Foggia, Viale Pinto, 1, Foggia, 71122, Italy, Tel +390881732205, Email giulia.ciccarese@unifg.it